Post-resuscitation syndrome after cardiac arrest - protecting vital organs and individualizing treatment - Seder, David (Henry Stewart Talks, 2016)
Acute myocardial infarction, Other organ systems in post-resuscitation syndrome, The individual pathophysiology of the patient, Classifying type and severity of injuries, Importance of etiology, Harm reduction